Microwave Tar Thermal Cracking System For A 10kw Downdraft Gasifier - Kamaluddin, Fazrullah (Universiti Sains Malaysia, 2019)
Biomass gasification is a promising way to utilize the producer gas (PG) for power generation in internal combustion engine and turbines. However, tar in the PG is a major drawback since it blocks the equipment when PG is cooled. In order to solve this problem, tar thermal cracking method is the preferred method to remove tar as it increases the heating value of the PG. Among all the tar thermal cracking methods, microwave (MW) tar thermal cracking is the best as it is more efficient and cost-effective. However, the current MW reactor which was developed earlier is only at lab-scale. Therefore, this project aims at upscaling the current MW reactor to allow a higher flow rate of PG through it during the tar cracking process. The biomass gasification system using a 10kW downdraft gasifier was characterized by finding the equivalence ratio (ER), PG composition and heating value as well as the gasifier cold gas efficiency. The existing MW reactor was upscaled and modified by installing an alumina reactor with bigger diameter in it to allow a higher flow rate of PG. The MW reactor was then integrated with the gasification system. MW tar thermal cracking was done at the reaction temperature of 1250°C with a constant residence time of 0.7s. The results showed that the gasification was performed in the optimum ER range which was 0.34 and resulted in producing PG with heating value of 4.79 MJ Nm-3. The cold gas efficiency obtained was high which was 84.92%. PG analysis revealed that the tar content in the PG was reduced from 1600 mg Nm-3 to 140 mg Nm-3 which corresponds to a conversion efficiency of 91.25% while the particulate content in the PG was reduced from 240mg Nm-3 to 12mg Nm-3 which corresponds to a conversion efficiency of 95% through the MW tar thermal cracking process. The PG composition was also changed since most of the tar and particulate had converted into useful combustible gases through the MW tar thermal cracking process. The PG composition analysis showed that the H2 and CO was increased while CH4 was reduced. The heating value of the PG was also increased from 4.79 MJ Nm-3 to 5.5 MJ Nm-3. The reduction of tar and particulate content in the PG together with the increase in the heating value of PG showed that the upscaled MW tar thermal cracking process was successful.